Estevão Silva e a pintura de naturezas mortas no Brasil do século XIX - Pessôa, Alexandre Neiva (2002)
Despite the recent historiographic interest in nineteenth-century Brazilian art, still-life painting remains almost an unexplored field. This research intends to displace the lack of studies on the theme by approaching the work of one of the most distinguished still-life painters among us, Estevão Roberto da Silva (1845-1891). Willing to measure his legacy to the National art, we have made up a reference table gathering the production of those preceded him in the specialty. Based on nine Estevão’s paintings analysis, we could find out that he renewed the conventions into ways: from the viewpoint of composition and brushwork.